2019
DOI: 10.1101/604991
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Clinical evaluation of presepsin considering renal function

Abstract: Presepsin, a glycoprotein produced during bacterial phagocytosis, has attracted attention as a sepsis marker for bacterial infections. However, since presepsin is affected by renal function, there is a need to separate the evaluation criteria for diagnosis of healthy subjects from that of patients with renal disorder. In this study, we analyzed the influence of kidney function on presepsin concentrations and recalculated the reference range based on the findings. For this purpose, EDTA-whole blood from 47 heal… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…The optimal cutoff value of PSS for diagnosis of sepsis was higher in patients with AKI than in those without it (828 pg/mL vs 694 pg/mL; P < .001). [27] Miyoshi et al [28] reported that PSS levels in patients with chronic kidney disease were significantly higher than in healthy volunteers. In our study, PSS levels were elevated in accordance with AKI severity.…”
Section: Discussionmentioning
confidence: 99%
“…The optimal cutoff value of PSS for diagnosis of sepsis was higher in patients with AKI than in those without it (828 pg/mL vs 694 pg/mL; P < .001). [27] Miyoshi et al [28] reported that PSS levels in patients with chronic kidney disease were significantly higher than in healthy volunteers. In our study, PSS levels were elevated in accordance with AKI severity.…”
Section: Discussionmentioning
confidence: 99%
“…[23] Presepsin, a glycoprotein produced during bacterial phagocytosis, is used as a sepsis marker for bacterial infections [24]. The meta-analysis demonstrates some mortality prediction value in presepsin in patients with sepsis [25].However, presepsin levels are affected by renal function, and the evaluation criteria according to kidney function or in chronic kidney diseases remain controversial [13].Previous studies show that presepsin has potential as a novel biomarker for the early diagnosis of sepsis [12].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, presepsin may represent a novel biomarker for the diagnosis of sepsis. Presepsin concentrations were positively correlated with a few biomarkers of renal function, indicating the necessity to consider the effect of renal function in patients with renal impairment [13].Studies have shown that presepsin level may increase to varying degrees in acute kidney injury (AKI) [1], which limits its use in the diagnosis of sepsis in this patient population. CKD has a high global prevalence with a consistent estimated global CKD prevalence of between 11 to 13% with the majority stage 3 [14].…”
Section: Introductionmentioning
confidence: 99%
“…13 Another study demonstrated that presepsin levels increase with a decrease in glomerular filtration rate )GFR(. 14 Patients with chronic renal failure were not included in our study. However, urea and creatine values were significantly different among the 3 groups in this study.…”
Section: Discussion Limited Studies Have Been Conductedmentioning
confidence: 99%